REVITALISASI MUTU PENDIDIKAN ANAK USIA DINI BERBASIS KARAKTER BUILDING DALAM MENINGKATKAN IPM DI KELURAHAN SUKA MAJU - Ulfah Sari Rezeki; Tina Sheba Cornelia; Siti Zahara. H. Harahap (Universitas Quality, 2021)
Character education is carried out with the aim of improving the quality of educational processes and outcomes that lead to the formation of character and morals of students as a whole, integrated and balanced in accordance with the competency standards of graduates in educational units. In addition, character education is also directed at developing moral intelligence (building moral intelligence) or developing the ability to understand right and wrong, namely having strong ethical beliefs and acting on these beliefs so that people behave right and respectfully. Revitalizing education needs to be done by applying a holistic and character-based learning model, revitalizing moral, value, religion and citizenship education, revitalizing family, school and community education, and revitalizing the role of mass media. This research was conducted to determine the contribution of character education in Kelurahan SukaMaju, to know the internilization of character education, and to find out the constraints and efforts that will be made in implementing character education in Kelurahan Like the Forward. Contributing thoughts for Kelurahan Suka Maju in implementing character education, especially the character of the nation. Data collection is collected in this study using measuring tools or research instruments such as: Interviews, questionnaires, and observations.